Karakterisasi Esktrak Air Teripang Emas (Stichopus hermanii) - Dian Widya Damaiyanti (Denta Journal Kedokteran Gigi, 2015)
Background: Indonesia is the country with the biggest sea cucumbers world’s producer. So far, sea cucumbers are only used as a side dish alone. Indonesia can provided added value and high economic value of gold sea cucumber through right procedure. A lot of gold sea cucumbers active substance that are suspected to have an influence on wound healing. For the best result, extract gold sea cucumber must be prepare with correct procedure. Water extract is one of a safe procedure with a small risk that may damage parts of the active substance. Purpose: The aim of this study is to know the characterization of water extract gold sea cucumber (Stichopus hermanii). Materials and Methods: Gold sea cucumbers were collected, homogenized with distillated water and shaken with water-bath shaker. Then extract was freeze dried, the result then characterized using spectrophotometer. Result: Thelargest component to fewest component of water extract gold sea cucumber is total protein 76,82%, essential amino acid 48,11%, non essential amino acid 28,70%, glycoprotein 4,62%, collagen 4,05%, GAG’s 1,62%, proteoglycan 1,13%, heparin sulfat 1,02%, calcium 59%, saponin 56%,heparin 38%, hyaluronat acid 29%, calcium 0,59%, Zinc 0,01%. Conclusion: There is many active substance of water extract gold sea cucumber that involed in wound healing process.